Voldtægtsforbrydelsen i retshistorisk belysning - Dübeck, Inger (Historisk Tidsskrift, 2013)
Rape in Legal HistorySanctions against rape can be found in even very old written legal sources, but the reasons behind the different reactions were varying. The present study discusses the following questions: Which was the view of rape and attempted rape in the Middle Ages and the Age of Reformation in relation to the view in the society of 18th and 19th century? Did the church and the secular society represent different conceptions of rape as a crime? The older societies are widely held to have been rather violent, and consequently one would expect a certain amount of rape cases in the court roles from that time. In fact such cases are rather rare before the 19th century. The article explains this scantiness as a result of the combination of a very serious punishment, normally death penalty, and the very heavy burden of proof, which laid with the injured woman.